Helmet use in skiing and snowboarding in Switzerland during the past 20 yearsPractical implications - S. Niemann; F. Bürgi; O. Brügger (Elsevier, 2023)
Summary: Objectives: The aim of this study was to quantify helmet use in skiing and snowboarding in Switzerland. Design: Regular cross-sectional surveys of skiers and snowboarders were conducted on Swiss slopes from the 2002/2003 to the 2021/2022 seasons. Method: Surveys included information on helmet use, sport, gender, age, skill level, and country of residence. Data from 15 single surveys were used to trace the evolution of helmet use in Switzerland. A logistic regression on data from the most recent survey was conducted to detect differences in helmet use among demographic groups. Results: In the 2002/2003 season, 14% of skiers (95% confidence interval [CI] ​= ​12%-18%) and 20% of snowboarders (CI 16%-26%) used a helmet. By the most recent season (2021/2022), wearing rates for both skiers and snowboarders had increased significantly (skiers: 95% [CI 93%-97%]; snowboarders: 92% [CI 89%-95%]). The regression results showed that skiers, females, younger people, and people in the German-speaking part of Switzerland were more likely to wear a helmet. Conclusions: The results show an impressive evolution of helmet use rates among skiers and snowboarders since the 2002/2003 season. Steep differences detected in earlier seasons have leveled out, and most people on the slopes today wear helmets. Nevertheless, the ongoing efforts for promoting helmet use should be maintained.